The Effect of PETTLEP-Based Visualization Training on the Self-Confidence Level of Pencak Silat Athletes - Megawati Agustiandho; Nidaul Hidayah; Muhamad Tafaqur (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
PETTLEP visualization is a mental training method that uses visualization techniques with a focus on seven main components: Physic, Environment, Task, Timing, Learning, Emotion, and Perspective. This practice aims to create a mental image that closely resembles the real situation during an activity or competition, helping to improve an athlete's performance and psychological aspects such as confidence and stress management. This study aims to determine the effect of PETTLEP-based visualization training on increasing the self-confidence of pencak silat athletes. Self-confidence is an important psychological aspect that influences an athlete's ability to manage stress, make the right decisions, and display optimal performance during competitions. The research method used a one-group pretest-posttest design with a sample of 13 athletes. The instrument used was a self-confidence questionnaire completed before and after the PETTLEP visualization intervention. The results of the descriptive analysis showed an increase in the average score from 32.15 in the pretest to 35.54 in the posttest. The normality test showed that the data were normally distributed, while the paired t-test showed a significance value of 0.000, confirming a difference in scores before and after the treatment. These findings prove that PETTLEP visualization training is effective in increasing the self-confidence of pencak silat athletes by helping them build stronger mental readiness, focus, and self-confidence. Therefore, PETTLEP visualization training is recommended for implementation in pencak silat athlete development programs.